Energy Efficiency of Tram Transport in the City of Osijek - Hrvoje Glavaš; Milan Ivanović (International Journal of Electrical and Computer Engineering Systems, 2013)
In the city of Osijek, tram transport started long before it was introduced in many European and world cities. This paper presents the ways to increase tram traffic energy efficiency in the city of Osijek. The tram transportation system as an urban way of traffic as well as plans for further development are described. Energy efficiency indicators are presented based on electricity consumption and the number of passengers in the past decade. The tram transport system is compared with other forms of public transport in the city of Osijek. An increase in energy efficiency in the sector of urban transport is proved based on the presented data.